Urdu adaptation and validation of a disease-specific quality-of-life questionnaire in a Pakistani population of Achalasia - Sameen Abbas; Syed Sikandar Shah; Tayyab Saeed Akhhtar; Kiran Hameed; Saima Mushtaq; Amjad Khan (PLoS ONE, 2025)
Background Achalasia, a rare esophageal disease marked by dysphagia, impacts health-related quality-of-life (HRQoL), measurable by disease-specific tools like achalasia-specific questionnaire (ASQ) that assess symptom severity and QoL. However, to ensure its reliability and validity across different populations, cross-cultural adaptation is necessary. So, for this reason, this study aimed to validate an Urdu-translated version of an ASQ in a Pakistani population of achalasia patients. Methodology A prospective cross-sectional study involving 52 participants was conducted at the Center for Liver and Digestive Diseases, Holy Family Hospital, Rawalpindi. ASQ was translated into the Urdu language by a forward-backwards translation process with expert input. Validation included factor analysis, known-group techniques, Cronbach’s alpha for reliability, and an independent t-test comparing ASQ scores with Eckardt scores for criterion validity. Results Among 52 participants (27 males, median age 30 years; 25 females, median age 48 years), 63.5% had Achalasia type I, 26.9% type II, and 9.6% type III. Factor analysis confirmed a well-defined construct with good validity, and internal consistency was strong (Cronbach’s alpha = 0.89). The ASQ scores significantly correlated with Eckardt scores (p < 0.05), confirming its validity. 73.1% of participants found the translated version easy and completed in a short time duration. Conclusion Urdu-translated ASQ proved to have good psychometric properties, with strong evidence of validity, reliability, and feasibility regarding health status in Pakistani achalasia patients. It can be recommended as a reliable QoL measure for clinical and research purposes. Future studies should explore its application in larger, more diverse cohorts and further refine its use in achalasia management.